Predominance of normal left ventricular geometry in the male 'athlete's heart'. Issue 16 (10th June 2014) - Utomi, Victor; Oxborough, David; Ashley, Euan; Lord, Rachel; Fletcher, Sarah; Stembridge, Mike; Shave, Rob; Hoffman, Martin D; Whyte, Greg; Somauroo, John; Sharma, Sanjay; George, Keith
Abstract : Aims: This study evaluated (a) global LV adaption to endurance versus resistance training in male athletes, (b) LV assessment using by modern imaging technologies and (c) the impact of scaling for body size on LV structural data. Methods: A prospective cross-sectional design assessed the LV in 18 elite endurance-trained (ET), 19 elite resistance-trained (RT) and 17 sedentary control (CT) participants. Standard 2D, tissue Doppler and speckle tracking echocardiography assessed LV structure and function. Indexing of LV structures to body surface area (BSA) was undertaken using ratio and allometric scaling. Results: Absolute and scaled LV end-diastolic volume (ET: 43.7±6.8; RT: 34.2±7.4; CT 32.5±8.9 mL/m 1.5 ; p<0.05) and LV mass (ET: 29.8±6.6; RT: 25.4±8.7; CT 25.9±6.4 g/m 2.7 ; p < 0.05) were significantly higher in ET compared with RT and CT. LV wall thickness were not different between ET and RT. 65% of ET and 95% of RT had normal geometry. Stroke volume was higher in ET compared with both RT and CT (p<0.05). Whilst regional tissue velocity data were not different between groups, longitudinal and basal circumferential strain (ε) was reduced in RT compared with ET. Conclusions: In this comprehensive evaluation of the male athlete's heart (AH), normal LV geometry was predominant in both athlete groups. In the ET, 30% demonstrated an eccentric hypertrophy with no concentric hypertrophy in RT. Cardiac ε data in RT require further evaluation, and any interpretation of LV size should appropriately index for differences in body size.